Anti-Corruption Policy Strategies for Nigeria towards National Development: Evidence from Least Corrupt Countries - Olaniyi, Adeniran Adetayo (American International Journal of Social Science Research, 2019)
Anti-corruption policy strategies in Finland and Singapore were examined, and lessons were drawn for Nigeria. Finland and Singapore were chosen because they are among the least fifth corrupt countries in the world from 2010 to 2017, and they have different norms. Another reason is that the norm in Finland is fairly similar to the norms of Sweden, Denmark, Norway, New Zealand, and Australia which are also among the least corrupt countries in the world, while the norm of Singapore is fairly similar to Hong Kong and Japan which are also among the least corrupt countries in the world. It was revealed that the case of Nigerian society is similar to that of Singaporean society. In Finland, it was observed that anti-corruption measures and institutions are weak as it does not have a separate unit dedicated to investigate or prosecute corruption-related offences, but there is a guiding principle such that anti-corruption measures are integrated into general good governance policy grounded on the rule of law. Also in Singapore, anti-corruption was achieved through anti-corruption policy that has been in existence since the year 1959, although there was a situation of deplorable condition and widespread corrupt practices, but the new government in the late 1950s set up a strategy which resulted that top political leaders set themselves as role models for civil servants and showing zero tolerance for corrupt behaviour. Finally, recommendations were suggested.